Discovery of novel quaternary ammonium derivatives of (3R)-quinuclidinyl amides as potent and long acting muscarinic antagonists. Issue 8 (15th April 2015) - Prat, Maria; Buil, María Antonia; Fernández, Maria Dolors; Tort, Laia; Monleón, Juan Manuel; Casals, Gaspar; Ferrer, Manuel; Castro, Jordi; Gavaldà, Amadeu; Miralpeix, Montserrat; Ramos, Israel; Vilella, Dolors; et al.
Graphical abstract: SAR around R 1, R 2 and R 3 are reported. Abstract: Novel quaternary ammonium derivatives of (3 R )-quinuclidinyl amides have been identified as potent M3 muscarinic antagonists with a long duration of action in an in vivo model of bronchoconstriction. The synthesis, structure–activity relationships and biological evaluation of this series of compounds are reported.